Two new species of Sphaerodoridae (Annelida) from the Gulf of Thailand - Plathong, Jintana; Plathong, Sakanan; Capa, María (Zootaxa, 2020)
Despite being a great species-rich area, the Gulf of Thailand has been relatively poorly studied and new species are awaiting to be described. In the present study two new species of Sphaerodoridae (Annelida), Geminofilum thailandica sp. nov. and Sphaerodoridium songkhlaensis sp. nov. were collected in shallow soft bottoms at Songkhla Sea. Geminofilum thailandica sp. nov. is characterised by bearing sessile and elongated dorsal macrotubercles, arranged in two transverse rows per segment, lacking other dorsal papillae, having parapodia with a single papilla at the base and compound chaetae with blades 4–6 times as long as wide and serration showing variation within fascicles. Sphaerodoridium songkhlaensis sp. nov. can be distinguished from other congeners by the singular morphology of the short stalked dorsal macrotubercles as inverted cones, with a conspicuous rim encircling the flattened distal surface, and two longitudinal rows of smaller sessile tubercles, as inverted cones, along ventrum, with four pairs of tubercles per segment. Chaetae show variation in the serration within fascicles. The present study highlights the need for further biodiversity studies on benthic communities in this area.